How similarities and differences between sports lead to talent transfer: A process approach - Pion, J.; Teunissen, J. W.; ter Welle, S.; Spruijtenburg, G.; Faber, I.; Lenoir, M. (Talent identification and development in sport. International perspectives, 2021)
In this chapter, we start by providing an overview of the traditional concept of product talent transfer and its underlying constructs. In the second part we will discuss a process approach to talent transfer. The evidence-based possibilities of using the approach and constructs along the talent pathway are presented by, among others, the sampling opportunities, the enlargement of a talent pool and the use of donor sports. The benefits and possible implementation in practice is then outlined using the Flemish Sportkompas and the Dutch Ecosystem for talent identification and development as applied examples.